One House of Worship with Many Roofs: Imposing Architecture to Mediate Sunni, Alevi, and Gülenist Islam in Turkey. (1st July 2019) - Andersen, Angela
In 2013, Turkish media announcements declared that a complex containing a mosque for Sunni prayer, a cemevi (ceremonial hall) for the Alevi Muslim minority, and a shared courtyard and kitchen was to be built in the Tuzluçayır district of Mamak, Ankara. Computer renderings displayed the relationship of the parts within the walled precinct as equal in scale and scope, but the clear power imbalance between government-supported Sunni mosques and marginalized Alevi cemevis across Turkey suggested that merging the two sites of Islamic practice might have assimilationist aims. Alevi groups, heterogeneously comprised of hereditary spiritual lineages with a variety of teachings and practices that typically eschew Sunni tenets, protested the assimilationist pressures of the 'mosque-cemevi' while it was being constructed. The impetus for the project came from Fethullah Gülen, the religious leader of the 'Hizmet' movement living in exile in the United States. Once in favour with the Adalet ve Kalkınma Party-ruled Turkish government, he was accused of terrorist involvement in 2014 and of instigating the failed coup attempt of July 2016. The mosque-cemevi was never completed. This article will examine how state-supported Sunni, Alevi, and Gülenist Muslim selves encountered the mosque-cemevi project, and its role in imposing intra-Islamic relations in the Turkish Republic.